Generic data storage-based dynamic mobile app for standardised electronic health records database. (8th November 2019) - Batra, Shivani; Sachdeva, Shelly; Bhalla, Subhash
Standardisation plays an important role in making healthcare application worldwide adaptable. It uses archetypes for semantic interoperability. In addition to the interoperability, a mechanism to handle future evolution is the primary concern for market sustainability. An application should possess dynamism in terms of the front end (user interface) as well as the back end (database) to build a future proof system. Current research aims to extend the functionality of prior work on HEALTHSURANCE with a search efficient generic storage and validation support. At application level, graphical user interface is dynamically built using knowledge provided by standards in terms of archetypes. At the database level, generic storage structure is provided with improved searching capabilities to support faster access, to capture dynamic knowledge evolution and to handle sparseness. A standardised format and content helps to uplift the credibility of data and maintains a uniform and specific set of constraints used to evaluate user's health. Architecture proposed in current research enables implementation of mobile app based on an archetype paradigm that can avoid reimplementation of the systems, supports migrating databases and allows the creation of future-proof systems.